Influence of Material Property and Geometry on Acoustic Wave Propagation - Vasile Nastasescu; Ghita Barsan; Oana-Alexandra Mocian (Science and Technology: Recent Updates and Future Prospects Vol. 10, 2024)
The numerical analysis by finite element method offers new and efficient possibilities for different parameter calculus of acoustics phenomena. This paper presents some authors’ results regarding numerical modelling of the acoustic wave propagation, using the Ansys program. The Ansys program has in its finite element library dedicated elements for plane and spatial problems and other specific facilities about which more information is presented in this paper. The acoustic wave propagation is studied under conditions of the existence of acoustic absorbing panels. Different materials are taken into account (aluminium, foam, oak, polystyrene) for considered acoustic absorbing panels. Also, different dimensions and different cases for fixing the panels were considered. The acoustic wave propagation was studied in stationary conditions and dynamic conditions at different values of sound frequencies. A comparative analysis is performed regarding the influence of different conditions on acoustic wave propagation. Our studies presented in this paper refer to acoustic propagation in an open space, like in airports or around acoustic sources placed in the open space. The aim of this paper is to offer our experience in this field for a numerical analysis of the ways for sound level reduction. Also, the facilities of the Ansys program for the solving of such problems are presented in a practical manner of use.